2020
DOI: 10.3390/v12111225
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Epitope (RNNQIPQDF) of Porcine teschovirus Induced a Group-Specific Antiserum: A Bioinformatics-Predicted Model with Pan-PTV Potential

Abstract: Porcine teschovirus (PTV) is an OIE-listed pathogen with 13 known PTV serotypes. Heterologous PTV serotypes frequently co-circulate and co-infect with another swine pathogen, causing various symptoms in all age groups, thus highlighting the need for a pan-PTV diagnostic tool. Here, a recombinant protein composed of a highly conserved “RNNQIPQDF” epitope on the GH loop of VP1, predicted in silico, and a tandem repeat of this epitope carrying the pan DR (PADRE) and Toxin B epitopes was constructed to serve as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous studies showed that antigenic drift, one of the major reasons for immune evasion, were mainly recognized in VP1 and VP2 [ 1 , 8 ]. Comparing to the other PTV-2 strains from China, 24 unique amino acid (aa) mutations were discovered in the VP1 region, and 12 unique aa mutations were discovered in the VP2 of isolate HeNZ1 (labeled with orange frame in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that antigenic drift, one of the major reasons for immune evasion, were mainly recognized in VP1 and VP2 [ 1 , 8 ]. Comparing to the other PTV-2 strains from China, 24 unique amino acid (aa) mutations were discovered in the VP1 region, and 12 unique aa mutations were discovered in the VP2 of isolate HeNZ1 (labeled with orange frame in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, phylogenetic analysis of VP1 has been used as a reliable approach for characterizing the PTV genotypes [1]. Also, neutralizing epitopes mainly locate within VP1 and VP2 [1,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Computational approaches have thus emerged as powerful options for effective and rapid development of infectious disease diagnostics. They can predict antigenic epitopes of target viral proteins ( 15 ) and prioritize diagnostic protein candidates. Computational-based approaches can alternately target viral proteins of interest using short peptide sequences, with high precision, even when the target protein is mixed with dense populations of irrelevant proteins, as described in this study.…”
Section: Introductionmentioning
confidence: 99%